A decomposition method for efficient manufacturing of complex parts. Issue 6 (19th September 2017) - Massoni, Brandon R.; Campbell, Matthew I.
ABSTRACT: This paper presents a method to decompose three dimensional complex parts into readily available stock material to take advantage of advanced joining to build up a rigid assembly. The method generates many alternative assemblies by decomposing the solid geometry iteratively with cutting planes. Each assembly is then evaluated based on cost. The process continues until the developed search algorithm converges on a near optimal solution. Application of this method will reduce material waste, thus reducing per part processing time, energy consumption, and associated production costs. Example parts for a variety of metals show how the computational tool finds near optimal solutions for complex three dimensional solids. GRAPHICAL ABSTRACT: